2006
DOI: 10.1080/13803390590949494
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Memory in HIV-1 Infection

Abstract: The cognitive deficits associated with HIV-1 infection are thought to primarily reflect neuropathophysiology within the fronto-striato-thalamo-cortical circuits. Prospective memory (ProM) is a cognitive function that is largely dependent on prefronto-striatal circuits, but has not previously been examined in an HIV-1 sample. A form of episodic memory, ProM involves the complex processes of forming, monitoring, and executing future intentions vis-à-vis ongoing distractions. The current study examined ProM in 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
172
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(191 citation statements)
references
References 29 publications
14
172
3
2
Order By: Relevance
“…Consistent with the findings of Shum et al (2004), our results showed a modest correlation between ProM and executive functions; however, ProM performance was also associated with performance in several neuropsychological domains, including attention, working memory, processing speed, and learning. Such associations are commensurate with conceptual models suggesting that optimal ProM functioning relies on multiple cognitive substrates (e.g., Carey et al, 2006). Interestingly, learning, but not delayed recall, uniquely predicted variance in ProM performance.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Consistent with the findings of Shum et al (2004), our results showed a modest correlation between ProM and executive functions; however, ProM performance was also associated with performance in several neuropsychological domains, including attention, working memory, processing speed, and learning. Such associations are commensurate with conceptual models suggesting that optimal ProM functioning relies on multiple cognitive substrates (e.g., Carey et al, 2006). Interestingly, learning, but not delayed recall, uniquely predicted variance in ProM performance.…”
Section: Discussionsupporting
confidence: 64%
“…Cognitive measures assessed the domains of information processing speed (Trail Making Test, Part A [Reitan and Wolfson, 1993], Symbol Search and Digit Symbol subtests of the WAIS-III [Wechsler, 1997a]); attention (Continuous Performance Test-Identical Pairs d-prime [Cornblatt et al, 1989], Digit Span Forward subtest of the WAIS-III [Wechsler, 1997a], Digit Span Distractibility distracted and non-distracted total scores [Oltmanns and Neale, 1975]); working memory (Letter Number Sequencing and Digit Span Backward subtests of the WAIS-III [Wechsler, 1997a]); learning (total immediate recall scores from the Hopkins Verbal Learning Test-Revised [Benedict et al, 1998], Logical Memory from the Wechsler Memory Scale-Third Edition [Wechsler, 1997b], and Brief Visuospatial Memory Test-Revised [Benedict, 1997]); memory (percent retention at delay for each of the learning tests); and executive functioning (Trail Making Test, Part B minus Part A [Reitan and Wolfson, 1993], Wisconsin Card Sorting Test-64 card version total correct [Kongs et al, 2000], Stroop Color-Word Interference Test interference measure [Golden, 1978], Controlled Oral Word Association Test FAS total correct [Benton and Hamsher, 1989] Raskin, 2004), which is a standardized, 30-minute task whose psychometric properties (Woods et al, in pressb) and construct validity are well supported (e.g., Carey et al, 2006;Woods et al, 2007a,b, Woods et al, in press-b). The MIST includes eight ProM tasks counterbalanced for 1) length of delay (2 or 15 minutes); 2) response type (verbal or action); and 3) cue type (time-based, e.g., "In 2 minutes, ask me what time this session ends," or event-based, e.g., "When I hand you a postcard, self-address it").…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations